2003
DOI: 10.1016/s0928-8244(03)00255-4
|View full text |Cite
|
Sign up to set email alerts
|

Epitope mapping of pneumococcal surface protein A of strain Rx1 using monoclonal antibodies and molecular structure modelling

Abstract: Pneumococcal surface protein A (PspA) is an antigenic variable vaccine candidate of Streptococcus pneumoniae. Epitope similarities between PspA from the American vaccine candidate strain Rx1 and Norwegian clinical isolates were studied using PspA specific monoclonal antibodies (mAbs) made against clinical Norwegian strains. Using recombinant PspA/Rx1 fragments and immunoblotting the epitopes for mAbs were mapped to two regions of amino acids, 1-67 and 67-236. The discovered epitopes were visualized by modellin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
14
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 40 publications
4
14
0
1
Order By: Relevance
“…The B cell epitope recognized by 18 of the 36 (50%) anti-PspA 3-286 mAbs localized to the region corresponding to aa 3-192 of PspA. The B cell epitopes recognized by the remaining 18 mAbs are spread across the surface-exposed portion of PspA (aa residues 1-288), which is consistent with previous studies (21,23,37). Anti-PspA mAbs that recognized PspA did not recognize its subfragments PspA and PspA 98 -192 (Table VI, groups 7 and 8).…”
Section: Pspa and B Cell Epitopessupporting
confidence: 90%
See 2 more Smart Citations
“…The B cell epitope recognized by 18 of the 36 (50%) anti-PspA 3-286 mAbs localized to the region corresponding to aa 3-192 of PspA. The B cell epitopes recognized by the remaining 18 mAbs are spread across the surface-exposed portion of PspA (aa residues 1-288), which is consistent with previous studies (21,23,37). Anti-PspA mAbs that recognized PspA did not recognize its subfragments PspA and PspA 98 -192 (Table VI, groups 7 and 8).…”
Section: Pspa and B Cell Epitopessupporting
confidence: 90%
“…One region comprised the first 115 amino acids of PspA, and the other was from aa 192-260 (21). In another study, Kolberg et al located the B cell epitopes to two regions (aa 1-67 and aa 67-236) that essentially cover the extracellular domain (23). Recently, Miyaji and colleagues demonstrated that aa 32-212 (region A) and aa 213-312 (region B) of PspA are equally immunogenic and that immunization of mice with these subfragments induced high Ab titers.…”
Section: Pspa and B Cell Epitopesmentioning
confidence: 99%
See 1 more Smart Citation
“…The extent of protection against systemic pneumococcal infection has been shown to be influenced by target antigen accessibility to circulating host antibodies (Gor et al, 2005). Flow cytometry is a technique that permits epitope analyses on a large number of live bacteria Kolberg et al, 2000Kolberg et al, , 2001Kolberg et al, , 2003. In the present study we have used both polyclonal and mAbs recognizing the pneumococcal enolase protein and other surface determinants.…”
mentioning
confidence: 99%
“…Other mAbs used were also produced at NIPH, Oslo, Norway. mAb 145,F-2 (IgM) reacts with the phosphorylcholine determinant (Kolberg et al, 1997a), mAb 149,B-3 (IgG2a) and 159,D-7 (IgG2a) detect epitopes on PspA (Kolberg et al, , 2003 and 230,B-9 (IgG1) reacts with heat-shock protein 70 from S. pneumoniae and other streptococci (Kolberg et al, 2000).Rabbit antisera. Rabbit sera were obtained after immunization with recombinant enolase protein, purified PspA or purified PspC.…”
mentioning
confidence: 99%